2020
DOI: 10.1002/cppb.20120
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Plant Root Nuclei for Single Cell RNA Sequencing

Abstract: The characterization of the transcriptional similarities and differences existing between plant cells and cell types is important to better understand the biology of each cell composing the plant, to reveal new molecular mechanisms controlling gene activity, and to ultimately implement meaningful strategies to enhance plant cell biology. To gain a deeper understanding of the regulation of plant gene activity, the individual transcriptome of each plant cell needs to be established. Until recently, single cell a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 18 publications
(23 reference statements)
0
31
0
Order By: Relevance
“…In plants, research that use isolated nuclei for microfluidics snRNA-seq methods remain very limited. Using the 10× Genomics Chromium system, an average of 1,126 expressed genes per nucleus were obtained using Arabidopsis roots [20,22].…”
Section: Discussionmentioning
confidence: 99%
“…In plants, research that use isolated nuclei for microfluidics snRNA-seq methods remain very limited. Using the 10× Genomics Chromium system, an average of 1,126 expressed genes per nucleus were obtained using Arabidopsis roots [20,22].…”
Section: Discussionmentioning
confidence: 99%
“…Using the 10× Genomics Chromium system, an average of 1,126 expressed genes per nucleus were obtained using Arabidopsis roots [20,22]. So far, most scRNA-seq analyses performed in plants used protoplasts from Arabidopsis plant tissues [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…After samples were filtered through miracloth and a 40 μ m strainer, they were washed to remove ambient RNA from cellular cytoplasm or that may have leaked from nuclei during the isolation process. Standard protocols for plant nuclei isolation include centrifugation steps that range between 500-1500 g, for 5-10 min [18,20,22,23]. In the nuclei washes we centrifuged samples at 600 g for 5 min, to minimize damage to nuclei while pelleting them at the bottom of the tubes.…”
Section: Nuclei Washesmentioning
confidence: 99%
“…As a proof-of-concept demonstration in plant, our results showed that protoplasting-free large-scale single-nucleus sequencing is sufficient for cell type classification and marker gene identification in Arabidopsis roots. As we are preparing this manuscript, several groups have also recently adopted the nuclei-based protoplasting-free strategy independently to investigate various plant tissues[35-39]. Eliminating protoplasting as a prerequisite would enable large-scale single-cell profiling on a wide range of tissues and plant species.…”
Section: Discussionmentioning
confidence: 99%